2021
DOI: 10.1039/d1tc00307k
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity reduction by nanostructuration in electrodeposited CuNi alloys

Abstract: In the last years, the use of inexpensive and scalable materials in the industry for thermoelectric applications has received great interest, such as CuNi alloys. In this work, nanocrystalline CuNi...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…The highest value is 7.0 mW m –1 K –2 , obtained in the sample under 773 K/35 MPa (Figure c). It is comparable to or even higher than the previously reported Cu–Ni-based values. ,,, It is noted that the highest porosity (25.2%) in the 673 K/15 MPa sample in our work does not deteriorate the power factor as happened before, , and still maintains the high value around 4.1 mW m –1 K –2 comparable to the counterparts in previous studies, as shown in Table S4.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The highest value is 7.0 mW m –1 K –2 , obtained in the sample under 773 K/35 MPa (Figure c). It is comparable to or even higher than the previously reported Cu–Ni-based values. ,,, It is noted that the highest porosity (25.2%) in the 673 K/15 MPa sample in our work does not deteriorate the power factor as happened before, , and still maintains the high value around 4.1 mW m –1 K –2 comparable to the counterparts in previous studies, as shown in Table S4.…”
Section: Resultssupporting
confidence: 90%
“…It is comparable to or even higher than the previously reported Cu−Ni-based values. 21,29,32,36 It is noted that the highest porosity (25.2%) in the 673 K/15 MPa sample in our work does not deteriorate the power factor as happened before, 60,61 and still maintains the high value around 4.1 mW m −1 K −2 comparable to the counterparts in previous studies, as shown in Table S4. The resultant zT increases when temperature increases, as shown in Figure 7a.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1F). 38,39 These diffraction peaks confirm the formation of a single solid solution phase with the FCC structure of CuNi alloy and complete conversion of metal ions into pure metal nanoparticles in CuNi/IL@MWCNTs. The crystalline size of CuNi/IL nanoparticles decorated on MWCNTs was calculated using the Debye–Scherrer formula and found to be 55 nm, which was in good agreement with the obtained AFM images.…”
Section: Resultsmentioning
confidence: 73%
“…[28,29,205] Other forms of nanostructuring materials result in more conventional but eco-friendly semiconductors are being revisited for thermoelectric applications recently. The effect of nanostructuration in semiconductors is shown for instance, in our work with CuNi, [206] where through nanostructuring the material, fairly good thermoelectric properties are achieved. Also through nanostructuration, the properties of Silicon, which is a very poor thermoelectric material in its bulk form, can be enhanced.…”
Section: Other Eco-friendly Thermoelectric Materialsmentioning
confidence: 76%